2019
DOI: 10.1111/pedi.12860
|View full text |Cite
|
Sign up to set email alerts
|

Benefit finding among parents of young children with type 1 diabetes

Abstract: Benefit finding, perceived positive effects of adversity, has been associated with psychological well-being in people with chronic illnesses and with better adherence for adolescents with type 1 diabetes (T1D). Our qualitative research with parents of young children (< 6 years old) with T1D indicated that benefit finding (BF) is a common parental coping mechanism, but no tools exist to measure BF in parents. We determined psychometric properties of the Diabetes Benefit Finding Scale for Parents (DBFS-P), a 16-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Accordingly, it is not known whether the use of higher level benefit‐finding processes are a result of or a precursor to enhanced well‐being. Existing research (e.g., Chiba et al, 2020; Lovell & Wetherell, 2020; Pierce et al, 2019; Sears et al, 2003; Wang & Hoyt, 2018; Willard et al, 2016) and family accounts in the present study may support the potential of benefit‐finding to promote well‐being. However, future longitudinal research is needed to provide a clearer understanding of causality.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Accordingly, it is not known whether the use of higher level benefit‐finding processes are a result of or a precursor to enhanced well‐being. Existing research (e.g., Chiba et al, 2020; Lovell & Wetherell, 2020; Pierce et al, 2019; Sears et al, 2003; Wang & Hoyt, 2018; Willard et al, 2016) and family accounts in the present study may support the potential of benefit‐finding to promote well‐being. However, future longitudinal research is needed to provide a clearer understanding of causality.…”
Section: Discussionsupporting
confidence: 64%
“…Evidence suggests the constant threat and emotional burden of raising children with food hypersensitivity weighs heavily on the psychological well-being of all family members (Broome-Stone, 2012; Chooniedass et al, 2020;Cummings et al, 2010;Knibb & Semper, 2013;Marklund et al, 2007). Similar to other unpredictable, chronic childhood conditions (Bellin & Kovacs, 2006), such as diabetes (Pierce et al, 2019), disabilities (McConnell et al, 2014), autism (Lovell & Wetherell, 2020), and cancer (Willard et al, 2016), research shows that psychosocial management is as essential as physical management when raising a child with food hypersensitivity (Chooniedass et al, 2020;DunnGalvin et al, 2009). If improperly managed, food hypersensitivity and the associated restrictive diet, social limitations, and psychological burden can contribute to a breakdown of family relationships and support systems (Cummings et al, 2010;Valentine & Knibb, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The baseline level of parental knowledge regarding a health-related intervention for children and corresponding health professionals' behaviour plays an important role to maintain parental adherence to the intervention (Lillo-Navarro et al, 2019). In addition, finding something positive from adverse life situations is a common psychological coping mechanism for parents of children with a chronic illness (Pierce et al, 2019). Supporting these ideas, we found that most participants thought knowledge regarding safety and potential health benefit related to a technique are important factors to involve children in research.…”
Section: Efficacy and Safetymentioning
confidence: 57%
“…Pierce and colleagues found that most parents of young children with T1D engaged in positive coping strategies [ 39 ], including defining a “new normal” for their family, engaging in creative problem-solving, and benefit finding (positive perceptions in the face of adversity). Expanding on the advantage of benefit finding in their later work, this group also found that benefit finding was correlated with higher parental diabetes self-efficacy [ 46 ]. Parental diabetes self-efficacy, defined as parents’ perceived ability to oversee diabetes care tasks, is an important component of managing diabetes for a young child [ 47 ].…”
Section: Parental Coping and Resiliencementioning
confidence: 99%